2015
DOI: 10.1088/0256-307x/32/11/116101
|View full text |Cite
|
Sign up to set email alerts
|

Local Five-Fold Symmetry and Diffusion Behavior of Zr 64 Cu 36 Amorphous Alloy Based on Molecular Dynamics

Abstract: A molecular dynamics simulation is performed to investigate the relationship between the local five-fold symmetry and the diffusion behavior involved in the rapid solidification of a Zr64Cu36 alloy melt. The Voronoi polyhedron analysis indicates that the icosahedral clusters cannot explain the total amorphous structure, while the local fivefold symmetry shows more advantage in describing the relationship between the transition of the clusters and the diffusion behavior of Zr64Cu36 amorphous alloy. It is found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Such correlation has also been observed in other MD simulations. [52] This tendency becomes more remarkable as 016104-4 temperature decreases (see Fig. 5).…”
Section:  W Mpassmentioning
confidence: 84%
See 1 more Smart Citation
“…Such correlation has also been observed in other MD simulations. [52] This tendency becomes more remarkable as 016104-4 temperature decreases (see Fig. 5).…”
Section:  W Mpassmentioning
confidence: 84%
“…Due to the incompatibility with translational symmetry, the five-fold symmetry results in severe frustration and hinders crystallization in colloids. [33,34] It is also verified that five-fold local symmetry plays a crucial role in dynamical arrest in colloidal and granular systems [43][44][45][46][47][48][49][50][51][52][53][54] and closely correlated with some properties such as fragility and boson peak. [46,47] Therefore, it is anticipated that local atomic symmetry could be a simple and general structural parameter in metallic liquids and glasses for better understanding the structure-property relationship in amorphous alloys.…”
Section: Introductionmentioning
confidence: 85%
“…For glassy systems, icosahedrons were believed to be of importance in featuring local structure, and therefore were often taken as the characteristic quantity to understand the relation between structure and dynamic properties. [30] More general, the dynamic properties were found to be closely related to the local five-fold symmetry associated with Voronoi polyhedron, [31] which is defined as…”
Section: Resultsmentioning
confidence: 99%
“…Experimental and numerical studies have found that the relative peak positions in RDFs of metallic glasses are identical with the values of their crystalline counterparts, which suggests that disordered systems may hide the translational order inherited from crystal phases. [31,32] It is possible that there is a competition between the five-fold symmetry and the crystalline ordering in metallic glasses. To some extent H atoms tend to bond to base elements, forming metal hydrides, in particular with Zr atoms.…”
Section: Resultsmentioning
confidence: 99%
“…In some special cases, such as the liquid alloy in rapid cooling solidification, the atoms in liquid alloy lacks sufficient time to achieve a completely ordered arrangement and crystallization, and may form a relatively stable amorphous alloy with a disordered solid state structure within a certain duration and temperature range. [1][2][3][4] The amorphous alloys differ from crystalline alloys by the former's lack of grain and grain boundary. Therefore, amorphous alloys possess many unique properties, such as excellent magnetism, corrosion resistance, and wear resistance; high strength, hardness, and toughness; and high resistivity and electromechanical coupling properties.…”
Section: Introductionmentioning
confidence: 99%